KEBERLANJUTAN PENATAAN LABEL RAMAH LINGKUNGAN DALAM MENDUKUNG KONSUMSI DAN PRODUKSI BERKELANJUTAN - Dhesinta Rini, Wafia Silvi; Lumban Gaol, Heru Saputra (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
Abstract Environmental protection instruments in Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) are divided into preventive and repressive. One of the preventive instruments in UUPPLH is an economic instrument. Environmentally friendly labels (ekolabels) are one part of the monetary instrument. The arrangement of ecologically friendly labels is needed to support sustainable consumption and production policies. However, there are still several problems with arranging environmentally friendly labels, one of which is the practice of greenwashing. This study focuses on the issue of whether the arrangement of ecologically friendly labels follows the direction of sustainable consumption and production policies and whether their implementation can reduce greenwashing activities. The method used in this study is normative juridical, which is carried out through a literature study using primary and secondary legal materials. The study's results indicate that the arrangement of voluntary environmentally friendly labels is still insufficient to reduce greenwashing practices, so sustainable consumption and production goals have not been optimally achieved.